2013
DOI: 10.1371/journal.pone.0057904
|View full text |Cite
|
Sign up to set email alerts
|

Is R2* a New MRI Biomarker for the Progression of Parkinson’s Disease? A Longitudinal Follow-Up

Abstract: PurposeTo study changes of iron content in basal ganglia in Parkinson’s disease (PD) through a three-year longitudinal follow-up of the effective transverse relaxation rate R2*, a validated MRI marker of brain iron content which can be rapidly measured under clinical conditions.MethodsTwenty-seven PD patients and 26 controls were investigated by a first MRI (t0). Longitudinal analysis was conducted among the 18 controls and 14 PD patients who underwent a second MRI (t1) 3 years after. The imaging protocol cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
142
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 38 publications
(49 reference statements)
18
142
2
4
Order By: Relevance
“…Several different techniques have been used to study other conditions that implicate abnormal iron deposition including AD and PD. MRI transverse relaxation rates R2 [42][43][44][45] and R2* 43,[46][47][48] correlate with brain iron concentration, although they are affected by tissue fluid content. Field dependent relaxation rate increase imaging (FDRI) 42,49,50 and quantitative susceptibility mapping (QSM) [51][52][53][54][55] are more recent advances in brain iron imaging.…”
Section: Other Mri Techniques Of Interestmentioning
confidence: 98%
“…Several different techniques have been used to study other conditions that implicate abnormal iron deposition including AD and PD. MRI transverse relaxation rates R2 [42][43][44][45] and R2* 43,[46][47][48] correlate with brain iron concentration, although they are affected by tissue fluid content. Field dependent relaxation rate increase imaging (FDRI) 42,49,50 and quantitative susceptibility mapping (QSM) [51][52][53][54][55] are more recent advances in brain iron imaging.…”
Section: Other Mri Techniques Of Interestmentioning
confidence: 98%
“…In addition, in a previous study, significant variation of R2* was longitudinally observed in the caudal putamen of patients with PD evolving during a 3-year period. 46 Therefore, additional longitudinal studies are needed to evaluate the relationship between the iron levels of the putamen and the severity of PD more comprehensively. Our retrospective study has some limitations.…”
mentioning
confidence: 99%
“…Over a 3-year follow-up, increased R2* in the substantia nigra correlated with the worsening of motor symptoms of PD, suggesting that R2* may be a biomarker of disease progression in PD (Ulla et al, 2013). Association between high R2* signal and LIDs has yielded inconsistent results either showing a positive (Bunzeck et al, 2013) or no correlations (Wieler, Gee, & Martin, 2015) between iron deposition and motor complications.…”
Section: Iron Deposition and Neuromelaninmentioning
confidence: 99%